Dissection of overlapping functions within the adenovirus type 5 E1A gene. - Winberg, G (1984)
The adenovirus E1A gene encodes multiple, overlapping mRNAs whose products function both to regulate mRNA levels during the lytic cycle of the virus and to facilitate transformation of non-permissive cells. To assign specific functions to the E1A gene products, two adenovirus type 5 variants have been constructed. Mutants dl347 and 348 carry cloned segments corresponding to the E1A 12 and 13S mRNAs, respectively, in place of the normal E1A gene. The variants produced the predicted E1A-specific mRNAs and polypeptides. Both viruses grew efficiently in HeLa cells. Although the 13S mRNA products were more effective, the products of either mRNA species could stimulate the accumulation of mRNAs from additional transcription units. Both viruses could induce the formation of transformed foci in an established rat cell line. Neither virus could transform primary rat embryo cells at normal frequency, and the dl347 foci which were induced were incomplete or abortive transformants. Thus, functions encoded by both 12S and 13S mRNAs are required for efficient and complete transformation of primary rat cells.